Antibody Responses in Patients with Staphylococcal Septicemia against Two Staphylococcus aureus Fibrinogen Binding Proteins: Clumping Factor and an Extracellular Fibrinogen Binding Protein - Colque-Navarro, Patricia (American Society for Microbiology, 2000)
We analyzed the serum antibody responses against two Staphylococcus aureus fibrinogen binding proteins, the cell-bound clumping factor (Clf) and an extracellular fibrinogen binding protein (Efb). The material consisted of 105 consecutive serum samples from 41 patients suffering from S. aureus septicemia and 72 serum samples from healthy individuals. An enzyme-linked immunosorbent assay (ELISA) was developed. Healthy individuals showed variable levels of antibodies against the studied antigens, and cutoff levels (upper 95th percentile) against these antigens were determined. No correlation was seen between serum antibody levels against Clf and Efb. In acute-phase samples 27% of patients showed positive antibody levels against Clf and 10% showed positive levels against Efb, while in convalescent-phase samples 63% (26 of 41) showed a positive serology against Clf and 49% (20 of 41) showed a positive serology against Efb. Antibody levels against Efb were significantly lower in the acute-phase sera than in sera from healthy individuals (P = 0.002). An antibody response against Clf was most frequent in patients suffering from osteitis plus septic arthritis and from endocarditis (80% positive). The antibody response against Efb appeared to develop later in the course of disease. A possible biological effect of measured antibodies was demonstrated with the help of an inhibition ELISA, in which both high-titer and low-titer sera inhibited the binding of bacteria to fibrinogen. In conclusion, we have demonstrated in vivo production of S. aureus fibrinogen binding proteins during deep S. aureus infections and a possible diagnostic and prophylactic role of the corresponding serum antibodies in such infections.